NILAI-NILAI KEHIDUPAN DALAM NOVEL DILAN, DIA ADALAH DILANKU TAHUN 1990 DAN IMPLEMENTASINYA PADA PEMBELAJARAN BAHASA INDONESIA - Farida Fitriani; Ani Endriani (Balai Bahasa Nusa Tenggara Barat, 2018)
The purpose of this study is to describe values of the life in the novel of “Dilan, Dia Adalah Dilanku Tahun 1990” and its implementation in Indonesian language learning at MAN 1 Lombok. The type of research used is qualitative method. The data are collected in the study throughreading method by tapping and note-taking techniques. Data analysis technique uses semiotic reading model, namely heuristic and hermeneutic readings. The validity of the data in this study is tsted by using triangulation techniques by applying the intrarater and interrater principles.The values of life in the novel of “Dilan, dia adalah Dilanku Tahun 1990” is social, democracy and love valueamong teenagers in that time. The values of life that can be modeled are the positive values, while the negative ones can be used as learning to avoid or not fall into things that are harmful to ourselves or others. The implementation of the values of life in the novel of“Dilan, dia adalah Dilanku Tahun 1990 at MAN 1 Lombok Tengah” has three stages of learning planning, namely the initial stage, the core, and the end.